Making Good Decisions: Television, Learning, and the Cognitive Development of Young Children - David C. Diehl; Stephanie C. Toelle (EDIS)
This series of publications by David C. Diehl and Stephanie C. Toelle addresses media and its effects on young children, from birth to age six. The series is designed to reach both professional educators and parents and to provide research summaries, tips for parents, and internet resources for further information. Published by the UF Department of Family Youth and Community Sciences, December 2008.